PKM Pelatihan Penulisan Artikel Ilmiah Sebagai Kiat Sukses Untuk Menulis PKM-AI dan PKM-GT bagi Mahasiswa - Sudarmanto Jayanegara; Wahyu Hidayat M; Muhammad Hasim; Baso Riadi Husda; Dary Mochamad Rifqie; B, Muhammad Fajar; Muh. Bhilal Halim (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Scientific article writing training is an important step in preparing quality PKM-AI and PKM-GT proposals. A good scientific article not only clearly and systematically describes the research, but also demonstrates its relevance and contribution in the chosen field. Therefore, students need to understand the basic concepts of writing scientific articles, the proper structure, and effective writing techniques and strategies. This research aims to provide the understanding and skills needed in writing scientific articles as tips for success in writing proposals for the Student Creativity Program (PKM) in Artificial Intelligence (PKM-AI) and Game Technology (PKM-GT). In an era of rapid technological development, PKM is a way for students to develop creative and innovative ideas related to AI and GT. Training methods include presentation sessions, discussions, and writing practice. Participants will be introduced to the main steps in writing scientific articles, including selecting topics, identifying research questions, reviewing the literature, developing a framework, collecting data, analyzing data, and discussing results. In addition, participants will be taught how to avoid plagiarism and adhere to scientific writing ethics. It is hoped that the results of this training will provide an in-depth understanding of writing scientific articles and improve participants' abilities in preparing strong PKM-AI and PKM-GT proposals. With good writing skills, students are expected to be able to present their ideas and contributions clearly, as well as gain support and recognition from institutions and related parties.